Advanced Voice and Multimedia Communications System for the ODOT ITS Network (FHWA-OK-08-04 2204) - (:unkn) unknown (My University, 2008)
Across the State of Oklahoma there are a multitude of agencies, at the federal, state, and local levels, all responsible for responding to emergency situations. Many of these agencies have a presence on the private ODOT ITS Network; however, these ITS console operators, heretofore, relied on public switched telephone network (PSTN) communications for coordination activities. In addition, many of these agencies use shortwave radios as a means of internal agency communication. Due to the independent nature of these agencies they are unable to communicate with each other using their agency specific radios. The goal of this project is to determine how these communication issues can be resolved by utilizing the large private ODOT ITS Network connecting these agencies. This work addressed both the ITS Network inter-console communication and the inter-agency radio voice bridging. In both cases, a low cost solution, as well as, preservation of the ITS Network integrity and security were primary considerations.
Keywords: intelligent transportation system; coice over internet protocol; radio bridging